2011
DOI: 10.1016/j.jds.2011.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of enamel matrix derivative and mineral trioxide aggregate on the mineralization potential of human cementum-derived cells

Abstract: KEYWORDS enamel matrix derivative; human cementumderived cells; matrix metalloproteinase-13; mineral trioxide aggregate Abstract Background/purpose: Cementogenesis is a critical event in the repair of endodontic perforations and the enamel matrix derivative (EMD) was reported to induce cementogenesis when used in periodontal disease. Yet, there is no study investigating the effects of EMD compared with mineral trioxide aggregate (MTA), a well-known material used for perforation repair. Because cementoblasts pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
2
4
0
Order By: Relevance
“…In our current study, OPN expression was found to be up-regulated in the MTA/BMP-2 and MTA/EMD groups on day 3, suggesting that the mineralization induced by combination of MTA and BMP-2 or EMD in MC3T3-E1 cells may promote OPN expression during an early stage. These findings are consistent with the results of a previous study that OPN is up-regulated in EMD-treated MTA groups on day 3 14. In our previous study, we found that MTA and EMD significantly stimulated the mineralization of human cementum-derived cells, which is consistent with the findings of Weishaupt et al who reported that the beneficial periodontal regeneration after treatment with EMD may be related to increased expression of the mineralization markers BSP and OPN at the mRNA level 31…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In our current study, OPN expression was found to be up-regulated in the MTA/BMP-2 and MTA/EMD groups on day 3, suggesting that the mineralization induced by combination of MTA and BMP-2 or EMD in MC3T3-E1 cells may promote OPN expression during an early stage. These findings are consistent with the results of a previous study that OPN is up-regulated in EMD-treated MTA groups on day 3 14. In our previous study, we found that MTA and EMD significantly stimulated the mineralization of human cementum-derived cells, which is consistent with the findings of Weishaupt et al who reported that the beneficial periodontal regeneration after treatment with EMD may be related to increased expression of the mineralization markers BSP and OPN at the mRNA level 31…”
Section: Discussionsupporting
confidence: 93%
“…Cementogenesis is a critical event in the repair of endodontic perforations, and EMD has been reported to induce cementogenesis when used for periodontal disease 13. The findings in our other study confirmed the capacity of MTA mixed with EMD to accelerate cementoblastic activity more than MTA alone and that EMD significantly stimulates the mineralization of human cementum-derived cells 14. The results of several previous studies have also suggested the beneficial effects of BMP-2 and EMD on hard tissue repair and regeneration.…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…In addition, the use of EMD to promote pulp stem cell proliferation and hard tissue regeneration in endodontic dentistry has recently been reported [26][27][28][29][30]. Conventionally, EMD was considered to be a material with great potential to enhance the regeneration of periodontal tissue [22][23][24][25]. In this study, we compared the biocompatibility and osteogenic potential of ProRoot MTA, RetroMTA, and Endocem MTA Premixed combined with Emdogain on hBMSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Enamel matrix derivative (EMD) is mostly composed of amelogenin and is known to contain growth factors. It has demonstrated significant potential in the regeneration of periodontal defects when applied to the root surface during periodontal surgery [22][23][24][25]. There are many recent reports regarding the use of Emdogain Gel (Straumann, Basel, Switzerland) in endodontics [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%